2016
DOI: 10.1117/12.2223671
|View full text |Cite
|
Sign up to set email alerts
|

On using multiple routing metrics with destination sequenced distance vector protocol for MultiHop wireless ad hoc networks

Abstract: A mobile ad hoc network is a collection of mobile nodes which communicate without a fixed backbone or centralized infrastructure. Due to the frequent mobility of nodes, routes connecting two distant nodes may change. Therefore, it is not possible to establish a priori fixed paths for message delivery through the network. Because of its importance, routing is the most studied problem in mobile ad hoc networks. In addition, if the Quality of Service (QoS) is demanded, one must guarantee the QoS not only over a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…If a node does not receive a Hello message from a neighbor within a fixed dead interval In addition, DSDV uses triggered updates when the network topology suddenly changes. If periodic and triggered updates occur in a short period of time, the values may be merged and only the periodic update will be performed [59,85]. In contrast, GPSRQ relies on the knowledge of the geographical position and state of links to neighbors, which provides a high level of network scalability.…”
Section: A Simulation Results and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…If a node does not receive a Hello message from a neighbor within a fixed dead interval In addition, DSDV uses triggered updates when the network topology suddenly changes. If periodic and triggered updates occur in a short period of time, the values may be merged and only the periodic update will be performed [59,85]. In contrast, GPSRQ relies on the knowledge of the geographical position and state of links to neighbors, which provides a high level of network scalability.…”
Section: A Simulation Results and Evaluationmentioning
confidence: 99%
“…4, where a lower value means a better quantum channel state. In the example shown in 2) The Public Channel Status Metric: Instead of using popular approaches from conventional or overlay networks [30,59], we use meta-data of keys such as the time duration of the key establishment process to effectively assess the state of the public channel. We define P m,s,i with Equation (7) to evaluate the state of the public channel between nodes s and i where T last,s,i is the length of time spent on the establishment of the key material at the time of measurement and T maximal,s,i is the maximum time that can be tolerated for the establishment of the key.…”
Section: B Qkd Link Metricmentioning
confidence: 99%
“…This paper addressed the question of the usability of destination-sequenced distance vector routing protocol routes. The work summarized the measurements that were performed using NS-3 v3.28 4 simulator with BRITE random topology generation. Our measurements of 3960 simulations, showed that, in general, 19.32% routes were used.…”
Section: Discussionmentioning
confidence: 99%
“…However, if possible, the node will strive to merge triggered and periodic changes into one packet to minimize the information being sent. The period in which such an approach is considered is 5 seconds before sending a periodic report [4], [13]. It is important to note that DSDV uses the same message format for both periodicals and triggered reporting.…”
Section: A Destination-sequenced Distance-vector Routing (Dsdv)mentioning
confidence: 99%
See 1 more Smart Citation